Pengaruh Pembelajaran Matematika Realistik Berbasis Macromedia Flash Terhadap Kemampuan Pemecahan Masalah SPLDV - Nilam Sari; Sudi Prayitno; Dwi Novitasari (Griya Journal of Mathematics Education and Application, 2026)
This study aimed to determine the effect of realistic mathematics education based on Macromedia Flash on eighth-grade students’ problem-solving ability in Systems of Linear Equations in Two Variables at MTsN 1 Bima in the 2025/2026 academic year. The study employed a quantitative quasi-experimental design. The population consisted of 110 eighth-grade students of MTsN 1 Bima. The samples were selected through cluster random sampling. Class VIII.1, consisting of 31 students, was assigned as the experimental class and received realistic mathematics education based on Macromedia Flash, while class VIII.4, consisting of 25 students, was assigned as the control class and received conventional learning based on Macromedia Flash. The research instrument was a posttest consisting of three essay questions. The data were analyzed using the t-test. The results showed that the average score of students’ problem-solving abilities in the experimental class was 85.937, while the control class obtained 79.16. Hypothesis testing showed that the = 4.461 and = 2.004 at a significance level of 0.05 (2-tailed). This finding indicates a significant difference between the two classes. Therefore, it can be concluded that realistic mathematics education based on Macromedia Flash significantly affects students’ problem-solving ability.